an=2×(10^n-1)/9
2=2×(10-1)/9
22=2×( 100-1)/9
222=2×(1000-1)/9
s=2/9×(10 100 1000 ... 10^n)-2n /9
a1=2=2*(10^1-1)/9
a2=22=2*(10^2-1)/9
a3=222=2*(10^3-1)/9
…
따라서: an=2*(10^n-1)/9 < / p>
Sn=a1 a2 …… an
=2*(10^1-1)/9 2*(10^2-1)/9 …… 2*(10^n -1)/9
=(2/9)*[(10^1 10^2 …… 10^n)-n]
=(2/9) * [10*(10^n-1)/9-n]
=(2/9)*[(10^(n 1)-10)/9-n], 2, an = 2×(10^n-1)/9
2=2×(10-1)/9
22=2×(100-1)/9
p>222=2×(1000-1)/9
s=2/9×(10 100 1000 ... 10^n)-2n/9
나머지 2에 대해 기하수열 공식을 사용하고 일반항을 찾습니다:
a1=2=2*(10^1-1)/9
a2=22 =2*(10^2-1)/9
a3=222=2*(10^3-1)/9
…
따라서: an=2*(10^n-1)/9
Sn=a1 a2 …… an
=2*(10^1-1)/9 2* (10^2-1)/9... 2*(10^n-1)/9
=(2/9)*[(10^1 10^2...,1 ,